Operational Performance Analysis of the Talud Tegak Wharf at the Public Port Owned by PT. Pelabuhan Indonesia (PELINDO) Gresik - Dwi Surya, Akbar; Dahri, Muhammad; Yudianto, Prima Yudha; Rakhman, Rizqi Aini (Journal of Engineering Science and Technology Management, 2026)
The Public Port of PELINDO Gresik is one of the strategic ports in East Java that functions as a major hub for regional cargo and logistics movement. Talud Tegak Wharf is one of the operational facilities that plays an important role in supporting cargo handling activities, particularly log timber commodities. This study aims to analyze the operational performance of Talud Tegak Wharf in supporting the smooth provision of port services. This research was conducted at Talud Tegak Wharf of the Public Port owned by PT Pelabuhan Indonesia (PELINDO) Gresik over a one-year observation period. The research employed a quantitative method using an operational performance analysis approach. Data were obtained through field observations and port operational records, analyzed then based on operational performance indicators, including vessel arrival trends, berthing time, cargo handling productivity, and berth utilization rate or Berth Occupancy Ratio (BOR). The analysis results were subsequently compared with port operational performance standards specified in the technical regulations of the Directorate General of Sea Transportation. The results indicate that the operational performance of Talud Tegak Wharf is in a good category. The average productivity of log timber cargo handling reached 63.52 m³/hour, exceeding the minimum operational performance standard. Meanwhile, the average BOR value of 82.04 percent indicates a high level of berth utilization while still remaining within safe limits. Overall, the analyzed operational performance indicators demonstrate that Talud Tegak Wharf has met the applicable port operational service performance standards at the Public Port of PELINDO Gresik